Differentiation of physical and chemical cross-linking in gelatin methacryloyl hydrogels - Lisa Rebers (Nature Portfolio, 2021)
Abstract Gelatin methacryloyl (GM) hydrogels have been investigated for almost 20 years, especially for biomedical applications. Recently, strengthening effects of a sequential cross-linking procedure, whereby GM hydrogel precursor solutions are cooled before chemical cross-linking, were reported. It was hypothesized that physical and enhanced chemical cross-linking of the GM hydrogels contribute to the observed strengthening effects. However, a detailed investigation is missing so far. In this contribution, we aimed to reveal the impact of physical and chemical cross-linking on strengthening of sequentially cross-linked GM and gelatin methacryloyl acetyl (GMA) hydrogels. We investigated physical and chemical cross-linking of three different GM(A) derivatives (GM10, GM2A8 and GM2), which provided systematically varied ratios of side-group modifications. GM10 contained the highest methacryloylation degree (DM), reducing its ability to cross-link physically. GM2 had the lowest DM and showed physical cross-linking. The total modification degree, determining the physical cross-linking ability, of GM2A8 was comparable to that of GM10, but the chemical cross-linking ability was comparable to GM2. At first, we measured the double bond conversion (DBC) kinetics during chemical GM(A) cross-linking quantitatively in real-time via near infrared spectroscopy-photorheology and showed that the DBC decreased due to sequential cross-linking. Furthermore, results of circular dichroism spectroscopy and differential scanning calorimetry indicated gelation and conformation changes, which increased storage moduli of all GM(A) hydrogels due to sequential cross-linking. The data suggested that the total cross-link density determines hydrogel stiffness, regardless of the physical or chemical nature of the cross-links.